2012
DOI: 10.5492/wjccm.v1.i2.40
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury classification: AKIN and RIFLE criteria in critical patients

Abstract: Acute kidney injury (AKI) is a common and serious complication in critically ill patients. The mortality rate remains high despite improved renal replacement techniques. A possible cause of the high mortality rate is that intensive care unit patients tend to be older and more debilitated than before. Pathophysiological factors associated with AKI are also implicated in the failure of other organs, indicating that AKI is often part of a multiple organ failure syndrome. Until recently, there was a lack of consen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
39
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 55 publications
0
39
4
1
Order By: Relevance
“…Acute kidney injury that developed during ECMO could be attributed to multiple factors such as sepsis, low cardiac output syndrome, exposure to nephrotoxic agents, and high intrathoracic pressures. 36 Previous studies have shown that the mortality associated with acute kidney injury was still high 37 and that the prognosis was related to age, acute physiology, and chronic health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute kidney injury that developed during ECMO could be attributed to multiple factors such as sepsis, low cardiac output syndrome, exposure to nephrotoxic agents, and high intrathoracic pressures. 36 Previous studies have shown that the mortality associated with acute kidney injury was still high 37 and that the prognosis was related to age, acute physiology, and chronic health status.…”
Section: Discussionmentioning
confidence: 99%
“…Acute kidney injury that developed during ECMO could be attributed to multiple factors such as sepsis, low cardiac output syndrome, exposure to nephrotoxic agents, and high intrathoracic pressures. 36 Previous studies have shown that the mortality associated with acute kidney injury was still high 37 and that the prognosis was related to age, acute physiology, and chronic health status.38 Therefore, it is necessary to screen for acute kidney injury throughout the time course to improve outcomes in this at-risk adult population. Finally, renal failure and the other major complications (gastrointestinal bleeding, intracranial bleeding and ischemic stroke) may all have intravascular origins in common.…”
mentioning
confidence: 99%
“…El criterio RIFLE fue publicado por el Acute Dialysis Quality Initiative group en 2004 (17) con la finalidad de estandarizar las definiciones de IRA. Posteriormente, en 2007, surgió la clasificación AKIN y ambas han probado su utilidad en determinar la severidad del daño renal en pacientes críticos (22,23) . Por otra parte, la clasificación AKIN no mejoró la sensibilidad ni la habilidad para predecir resultados en pacientes graves.…”
Section: Discussionunclassified
“…Clinical outcomes—Clinical outcomes in the FISSH pilot trial will reflect outcomes for the main trial which will include: hospital mortality, RRT use for AKI during 30-day period postrandomisation (including continuous renal replacement therapy or conventional haemodialysis), proportion of patients with RIFLE stage renal failure, 11 30-day mortality, ICU and hospital length of stay (censored at 30 days), ventilator-free days in the first 30 days postrandomisation and safety outcomes (acidosis and electrolyte imbalance postrandomisation).…”
Section: Methodsmentioning
confidence: 99%